Dynamics of transient metastable states in mixtures under coupled phase ordering and chemical demixing - Soulé, Ezequiel Rodolfo (2011)
We present theory and simulation of simultaneous chemical demixing and phase ordering in a polymer-liquid crystal mixture in conditions where isotropic-isotropic phase separation is metastable with respect to isotropic-nematic phase transition. In the case the mechanism is nucleation and growth, it is found that mesophase growth proceeds by a transient metastable phase that surround the ordered phase, and whose lifetime is a function of the ratio of diffusional to orientational mobilities. In the case of spinodal decomposition, different dynamic regimes are observed depending on the mobility ratio: metastable phase separation preceding phase ordering, phase ordering preceding phase separation, or simultaneous phase ordering and phase separation. Not only the overall dynamics but also the final structure of the material can be different for each kinetic regime.